2012
DOI: 10.1002/14651858.cd007675.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interactive computer-based interventions for weight loss or weight maintenance in overweight or obese people

Abstract: Background The World Health Organization (WHO) estimates that the number of obese or overweight individuals worldwide will increase to 1.5 billion by 2015. Chronic diseases associated with overweight or obesity include diabetes, heart disease, hypertension and stroke. Objectives To assess the effects of interactive computer-based interventions for weight loss or weight maintenance in overweight or obese people. Search methods We searched several electronic databases, including CENTRAL, MEDLINE, EMBASE, CIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
221
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(247 citation statements)
references
References 135 publications
16
221
2
8
Order By: Relevance
“…In the present paper, only food behaviour/weight loss-related interventions are explored. A Cochrane meta-analysis of weight loss/maintenance trials by Weiland et al (41) revealed that webbased interventions resulted in greater weight loss when compared with control conditions but significantly less weight loss compared with face-to-face interventions. This is similar to findings from four other meta-analyses (41)(42)(43)(44) .…”
Section: Web-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper, only food behaviour/weight loss-related interventions are explored. A Cochrane meta-analysis of weight loss/maintenance trials by Weiland et al (41) revealed that webbased interventions resulted in greater weight loss when compared with control conditions but significantly less weight loss compared with face-to-face interventions. This is similar to findings from four other meta-analyses (41)(42)(43)(44) .…”
Section: Web-based Interventionsmentioning
confidence: 99%
“…A Cochrane meta-analysis of weight loss/maintenance trials by Weiland et al (41) revealed that webbased interventions resulted in greater weight loss when compared with control conditions but significantly less weight loss compared with face-to-face interventions. This is similar to findings from four other meta-analyses (41)(42)(43)(44) . Reed et al (42) conducted a meta-analysis of eleven randomised controlled trials and reported additional weight loss when web-based interventions were used to supplement face-to-face interventions; however, substituting face-toface interventions with web-based interventions resulted in significantly less weight loss.…”
Section: Web-based Interventionsmentioning
confidence: 99%
“…Such applications (or "apps") provide an attractive, low cost, self-delivered way to prompt and support users to change their own behaviour, with minimal or no professional contact. They can employ a range of interactive behaviour change techniques (Bennett et al, 2010;Gabriele, Carpenter, Tate, & Fisher, 2011;Rothert et al, 2006;Wieland et al, 2012) and may be used continually over years if they engage users. For example, smartphone apps can provide personal tailoring of information, 24-hour availability to self-monitoring statistics, anonymity, online social support networks and affordability.…”
Section: Introductionmentioning
confidence: 99%
“…E-health interventions have been found to be effective in facilitating change across a range of health behaviours including weight loss and diabetes self-management (e.g. Gabriele et al, 2011;Munoz et al, 2006;Tang, Abraham, Greaves & Yates, 2014;Wieland et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches can be web-based [3], SMS based [43], mobile based [5,46], and furthermore can be based on different analytical methodologies [12,13,49]. There is also an increasing focus on techniques that utilize a smartphone in order to provide an e-coach service [9-11, 25, 30, 50].…”
Section: Background and Introductionmentioning
confidence: 99%